Clinical and molecular description of the first Italian cohort of 33 subjects with hypophosphatasia - Cinque, Luigia; Pugliese, Flavia; Salcuni, Antonio Stefano; Trombetta, Domenico; Battista, Claudia; Biagini, Tommaso; Augello, Bartolomeo; Nardella, Grazia; Conti, Francesco; Corbetta, Sabrina; Fischetto, Rita; Foiadelli, Thomas; et al. (Frontiers in Endocrinology, 2023)
Hypophosphatasia (HPP) is a rare genetic disease caused by inactivating variants of the ALPL gene. Few data are available on the clinical presentation in Italy and/or on Italian HPP surveys. Thirty suspected HPP patients were recruited from different Italian tertiary cares. Biological samples, and related clinical, biochemical and anamnestic data were collected and ALPL gene sequenced. Search for large genomic deletions at the ALPL locus (1p36) was done. Phylogenetic conservation and modelling were applied to infer the effect of the variants on the protein structure. Twenty-one ALPL variants and 1 large genomic deletion were found in 20 out of 30 patients. Unexpectedly, NGS-driven differential diagnosis allowed uncovering 3 hidden additional HPP cases, for a total of 33 HPP subjects. Eight out of 24 coding variants were novel and classified as “pathogenic”, “likely pathogenic” and “variants of uncertain significance”. Bioinformatic analysis confirmed all the variants strongly destabilize the homodimer structure. Ten cases with low ALP and high VitB6 resulted negative to genetic testing while 2 positive cases have an unexpected normal ALP value. No association was evident with other biochemical/clinical parameters. We present the survey of HPP Italian patients with the highest ALPL mutation rate so far reported and confirm the complexity of a prompt recognition of the syndrome, mostly for HPP in adults. Low ALP and high VitB6 values are mandatory for the genetic screening, this latter remaining the gold standard not only to confirm the clinical diagnosis but also to make differential diagnosis, to identify carriers, to avoid likely dangerous therapy in unrecognized cases.